PRESUPOSISI DALAM VIDEO PODCAST DENNY SUMARGO BERJUDUL “TIKTOK DI-BANNED HARI INI JADI PEMBUNUH UMKM” - Wijayanti, Tuti; Shafariana, Shafariana (Fakultas Teknik Universitas Negeri Makassar, 2025)
Abstract: This study analyzes the form and function of presuppositions in Denny Sumargo's video podcast entitled “TikTok Banned Today, Killing MSMEs” as part of the digital discourse discussing the polemic surrounding the ban on TikTok Shop in Indonesia. Previous studies on presuppositions in digital media have generally focused on static texts and entertainment content, and have not examined the use of presuppositions as a strategy for framing digital economic policy issues. This study aims to identify the types of presuppositions and explain their role in constructing representations of MSMEs and government regulations. Using a descriptive qualitative method, data was collected through listening and note-taking techniques on video transcripts lasting approximately 1 hour and 21 minutes. Relevant utterances were analyzed based on six categories of presuppositions according to Yule (1996), including existential, factual, non-factual, lexical, structural, and counterfactual presuppositions. A total of fourteen utterances were selected purposively and interpreted contextually to examine the discursive strategies used by the speakers. The results of the study show that all types of presuppositions appear in podcasts, with a predominance of existential and factual presuppositions. Both types serve to affirm the existence of losses suffered by MSMEs, TikTok Shop practices, and the urgency of regulation as facts that must be accepted by the audience. Meanwhile, lexical and structural presuppositions normalize the narrative of TikTok's threat to the local market, and non-factual and counterfactual presuppositions are used to convey risks and hypothetical scenarios that strengthen the persuasiveness of the discourse. These findings show that in digital discourse, presuppositions are not only devices of meaning but also framing instruments that influence how the public interprets digital economic policies. This research contributes to strengthening pragmatic studies in the context of new media and opens up opportunities for further research on the use of presuppositions on various other digital platforms.